MENGUKUR DAMPAK MAKROEKONOMI MASA COVID-19 PADA VOLATILITAS INDEKS SAHAM SYARIAH - Ani Sofia Diyani (UIN Siber Syekh Nurjati Cirebon, 2023)
The moment of the year-end holiday an triggered Increase in Covid-19, it will be a new anxiety for Indonesia such as in 2020 th and it can be a threat economy of Indonesia. So, this research purpose is to analyze the differences between the effects of Covid-19 and before Covid-19 appeared. The data used in research is macroeconomy which is BI Rate, Inflation, and an Index JII.The method in the research used the independent t-test and related sample t-test to analyze before and after Covid-19. The result is that JII and BI rates have the significant different before and after COVID-19 and The variable Inflation hasn’t any different in before and after Covid-19 coming.